PENGUATAN HUBUNGAN ANTARA LEADERSHIP STRATEGY, KNOWLEDGE MANAGEMENT DAN ORIENTASI BISNIS TERHADAP KINERJA UKM - Rukaiyah, St.; Muliana, Muliana (JURNAL MANAJEMEN BISNIS, 2018)
In theory there are only 2 types of business typologies, namely craftsman entrepreneur and opportunistic entrepreneur. Both have unique and different characteristics in carrying out the pace of their business, including the technical and strategic steps to determine a sustainable business. In this case the pattern of leadership and knowledge of business and business orientation certainly plays its role which in turn will provide final confirmation of the sustainability of a business activity. The purpose of this study is to analyze the extent of leadership roles, knowledge of management and business orientation towards business performance. This study took a sample of business people with SME status in Makassar City. Research approach with quantitative analysis with linear regression analysis method. The results of this study stated that leadership strategy, knowledge management and business orientation had no significant effect on the performance of SMEs.